PENDEKATAN ERGONOMI TOTAL UNTUK MENGANTISIPASI RISIKO KERACUNAN PESTISIDA PADA PETANI-PETANI BALI - Susy Purnawati (Bumi Lestari Journal of Environment, 2008)
Demands towards the increase of high profits and the safety of the agricultural product have made the use of pesticide unavoidable. Regulation and government effort to prevent farmers from the dangerous use of pesticide has long been implemented but the fact is that until nowadays the use of the pesticide by farmers is far from safety standard. Both the effect of acute and chronic pesticide intoxication can create nervous system disorder and even death. Most users do not have enough knowledge about the danger of the pesticide and safety work procedure. In order to increase the quality of the farmers’ health and to prevent them from the effect of acute intoxication and long term use of pesticide effect, it is necessary to develop strategies to anticipate the effect of pesticide through Total Ergonomic Approach. This approach (TEA) includes SHIP approaches (Systemic, Holistic, Interdisciplinary and Participatory) and Appropriate Technology assessment in design.Based on the anticipating strategies towards the effect of pesticide intoxication on the farmers it is hoped that in the future the use of pesticide can fulfill safety standard and increase the life quality of farmers and community in general.